1987
DOI: 10.1002/ajmg.1320270105
|View full text |Cite
|
Sign up to set email alerts
|

Duplication 3p21→3pter and cyclopia

Abstract: We report on a patient with an interchromosomal duplication of 3p, from 3p21 to 3pter, which apparently arose de novo. The infant had multiple malformations including holoprosencephaly and cyclopia. It is possible that duplication 3p has a generalized effect on the holoprosencephalon or the cleavage of the embryonic forebrain. Fibroblasts from the patient are available from the NIGMS Human Genetic Mutant Cell Repository (GM 7216).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Reports of individuals with duplications restricted to only chromosome 3p are much more rare [Gillerot et al, 1987;Kurtzman et al, 1987]. The common malformations seen in partial trisomy 3p include psychomotor and mental retardation, a short neck, hypertelorism and/or telecanthus, cleft lip/palate, microcephaly, short stature, a characteristic face with full cheeks, gastrointestinal malformations and congenital heart defects [Conte et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…Reports of individuals with duplications restricted to only chromosome 3p are much more rare [Gillerot et al, 1987;Kurtzman et al, 1987]. The common malformations seen in partial trisomy 3p include psychomotor and mental retardation, a short neck, hypertelorism and/or telecanthus, cleft lip/palate, microcephaly, short stature, a characteristic face with full cheeks, gastrointestinal malformations and congenital heart defects [Conte et al, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the karyotype and phenotype of the present case and 10 previously reported cases with simultaneous occurrence of dup(3p) and del(7q) (Pfitzer et al, 1982;Kurtzman et al, 1987;Bü rrig et al, 1989;Kent et al, 1990;Gurrieri et al, 1992;Kuller et al, 1992;Van Zalen-Sprock et al, 1995;Chen et al, 1996;Vance et al, 1998). Eight cases were associated with cyclopia, two with HPE-premaxillary agenesis (PMA) and one with cebocephaly.…”
Section: Discussionmentioning
confidence: 82%
“…Chen et al (1996) additionally reported two sib cases of der(2)t(2;3)(q37;p21)pat, one with cyclopia and the other with HPE-PMA. The presence of HPE as well as other mid-line developmental defects, such as cardiac anomalies, cleft lip and palate, meningocoele and hypospadias in patients with duplication 3p syndrome suggests that dup(3p) may result in dysmorphogenesis of the mid-line development field (Kurtzman et al, 1987;Lurie, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps more restricted breakpoints within 7q36 lead to aberrant expression of SHH due to a positional effect as proposed by Belloni et al 1996, or there may be an imprinting effect with disruption of an imprinting domain as suspected for Prader-Willi and Angelman syndromes on chromosome 15 [Lalande, 1994]. Another consideration for cell lines GM10064, GM7216, and V-1 is the interaction of partial monosomy of 7q and the dosage effect of partial trisomies of 13q and 3p, since both trisomies have been associated with the HPE phenotype [Roach et al, 1977;Kurtzman et al, 1987;Berry et al, 1990]. Analysis of the Sonic hedgehog gene in these cell lines is underway.…”
Section: Discussionmentioning
confidence: 99%